Inflammatory Bowel Disease Management During the COVID-19 Outbreak: The Ten Do's and Don'ts from the ECCO-COVID Taskforce. (29th July 2020) - Magro, F; Rahier, J-F; Abreu, C; MacMahon, E; Hart, A; van der Woude, C J; Gordon, H; Adamina, M; Viget, N; Vavricka, S; Kucharzik, T; Leone, S; et al.
Abstract: Our knowledge of COVID-19 is changing and evolving rapidly, with novel insights and recommendations, almost on a daily basis. It behooves the medical community to provide updated information on a regular basis, on best practice to facilitate optimal care of infected patients and on appropriate advice for the general population. This is particularly important in the case of patients with chronic conditions, such as inflammatory bowel disease [IBD]. In this review, we have compiled existing evidence on the impact of COVID-19 in IBD patients and provide guidance on the most appropriate care to adopt during the pandemic. Our review highlights that IBD, per se, is not a risk factor for COVID-19. However, all IBD patients with symptoms should be tested for SARS-CoV-2 and the procedures for disease management should be carefully adapted: [i] in SARS-CoV-2-positive IBD patients, medical treatments should be re-evaluated [with a particular focus on corticosteroids] always with the purpose of treating active disease and maintaining remission; [ii] non-urgent surgeries and endoscopic procedures should be postponed for all patients; [iii] online consultancy should be implemented; and [iv] hospitalization and surgery should be limited to life-threatening situations.